Immunohistochemical localization of mdm-2, p27Kip1 and bcl-2 in Warthin's tumor of the parotid gland - Elshafei Marwa M; Abd-Elhamid Ehab S (BMC, 2009)
Abstract Background Warthin's tumor is a benign monomorphic adenoma with unclear origin that almost occur exclusively in the parotid gland. Etiology of Warthin's tumor as well as its malignant potential are still unclear. Therefore immunohistochemical assessment of Warthin's tumor may be useful to detect its origin or its malignant transformation potential. Aims and objectives The present study aims to investigate the immunohistochemical expression of murine double minute-2 (mdm-2), p27Kip1 and B cell lymphoma-2 (bcl-2) in Warthin's tumor of parotid gland and also to clarify the role of these proteins in the behavior of that tumor. Methods Twenty paraffin blocks of cases previously diagnosed as Warthin's tumor were collected for immunohistochemical staining with primary antibodies against mdm-2, p27Kip1 and bcl-2 using streptavidin-biotin immunoperoxidase staining system. Results All cases showed immunopositivity for mdm-2 and p27Kip1 while 18/20 showed bcl-2 immunopositivity. Both layers of the neoplastic epithelial cells that line the cystic spaces showed immunopositivity with all antibodies used. Goblet cells were mdm-2 immunonegative while myoepithelial cells were p27Kip-1 immunonegative. Areas of epithelial proliferation that formed buds were p27Kip-1 and bcl-2 immunopositive. Conclusion Mdm-2 played a tumor-suppressor role that might be implicated with the benign behavior of Warthin's tumor. The mutual expression of both p27Kip1 and bcl-2 suggested a protective role of these slowly proliferating cells from apoptosis to maintain their survival and elevated bcl-2 expression offers a significant protection against p27Kip1-mediated apoptosis.